Environmental Enrichment and Estrogen Upregulate Beta-Hydroxybutyrate Underlying Functional Improvement - Pyo, Soonil; Kim, Joohee; Hwang, Jihye; Heo, Jeong Hyun; Kim, Kyungri; Cho, Sung-Rae (Frontiers in Molecular Neuroscience, 2022)
Environmental enrichment (EE) is a promising therapeutic strategy in improving metabolic and neuronal responses, especially due to its non-invasive nature. However, the exact mechanism underlying the sex-differential effects remains unclear. The aim of the current study was to investigate the effects of EE on metabolism, body composition, and behavioral phenotype based on sex. Long-term exposure to EE for 8 weeks induced metabolic changes and fat reduction. In response to the change in metabolism, the level of βHB were influenced by sex and EE possibly in accordance to the phases of estrogen cycle. The expression of β-hydroxybutyrate (βHB)-related genes and proteins such as monocarboxylate transporters, histone deacetylases (HDAC), and brain-derived neurotrophic factor (BDNF) were significantly regulated. In cerebral cortex and hippocampus, EE resulted in a significant increase in the level of βHB and a significant reduction in HDAC, consequently enhancing BDNF expression. Moreover, EE exerted significant effects on motor and cognitive behaviors, indicating a significant functional improvement in female mice under the condition that asserts the influence of estrogen cycle. Using an ovariectomized mice model, the effects of EE and estrogen treatment proved the hypothesis that EE upregulates β-hydroxybutyrate and BDNF underlying functional improvement in female mice. The above findings demonstrate that long-term exposure to EE can possibly alter metabolism by increasing the level of βHB, regulate the expression of βHB-related proteins, and improve behavioral function as reflected by motor and cognitive presentation following the changes in estrogen level. This finding may lead to a marked improvement in metabolism and neuroplasticity by EE and estrogen level.